The complexity of interaction between social media platforms and organizational performance - Ammar Ali Alalawneh; Saleh Yousef Y. Al-Omar; Saleh Alkhatib (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Social media platforms (SMPs) have become a key source of success for many organizations in today's complex business environment due to advancements in information and communication technologies that have created dynamic innovations. This study aims to explore the complex relationships between SMPs' usage and organizational performance with respect to small and medium-sized restaurants in Jordan. In addition, it investigates the impact of competition intensity as a moderating variable. The model of the study was assessed and examined by gathering data from 331 Jordanian restaurants using the partial least squares (PLS) method. The findings revealed that SMPs' usage is positively associated with restaurant performance (financial, marketing, and operational). In addition, the results indicate a significant moderating impact of competition intensity only on the relationship between SMPs' usage and restaurants' marketing performance. Based on the results, several theoretical and practical implications for restaurants have been suggested, as well as further research avenues.
Keywords: 650; competition intensity; Jordan; open innovation; organizational performance; SME restaurants; social media; social media platforms